Effects of early aldosterone antagonism on cardiac remodeling in rats with aortic stenosis-induced pressure overload. (1st November 2016) - Okoshi, M.P.; Cezar, M.D.M.; Iyomasa, R.M.; Silva, M.B.; Costa, L.C.O.; Martinez, P.F.; Campos, D.H.S.; Damatto, R.L.; Minicucci, M.F.; Cicogna, A.C.; Okoshi, K.
Abstract: Aldosterone plays a pivotal role in the pathophysiology of systolic heart failure. However, whether early aldosterone antagonism improves cardiac remodeling during persistent pressure overload is unsettled. We evaluated the effects of aldosterone antagonist spironolactone on cardiac remodeling in rats with ascending aortic stenosis (AS). Methods: Three days after inducing AS, weaning rats were randomized to receive spironolactone (AS-SPR, 20 mg/kg/day) or no drug (AS) for 18 weeks, and compared with sham-operated rats. Myocardial function was studied in isolated left ventricular (LV) papillary muscles. Statistical analyses: ANOVA or Kruskal–Wallis tests. Results: Echocardiogram showed that LV diastolic (Sham 8.73 ± 0.57; AS 8.30 ± 1.10; AS-SPR 9.19 ± 1.15 mm) and systolic (Sham 4.57 ± 0.67; AS 3.61 ± 1.49; AS-SPR 4.62 ± 1.48 mm) diameters, left atrial diameter (Sham 5.80 ± 0.44; AS 7.15 ± 1.22; AS-SPR 8.02 ± 1.17 mm), and LV mass were higher in AS-SPR than AS. Posterior wall shortening velocity (Sham 38.5 ± 3.8; AS 35.6 ± 5.6; AS-SPR 31.1 ± 3.8 mm/s) was lower in AS-SPR than Sham and AS; E/A ratio was higher in AS-SPR than Sham. Developed tension was lower in AS and AS-SPR than Sham. Time to peak tension was higher in AS-SPR than Sham and AS after post-rest contraction. Right ventricle weight was higher in AS-SPR than AS, suggesting more severe heart failure in AS-SPR than AS. Interstitial collagen fractional area and myocardial hydroxyproline concentration were higher in AS than Sham. Metalloproteinase-2 and -9 activity, evaluated by zymography, did not differ between groups. Conclusion: Early spironolactone administration causes further hypertrophy in cardiac chambers, and left ventricular dilation and dysfunction in rats with AS-induced chronic pressure overload.